2016
DOI: 10.1159/000445972
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia<b> </b>Is Separated into Two Subgroups Associated with Survival by <b><i>BCR</i></b>-<b><i>ABL</i></b> Fluorescence in situ Hybridization of Segmented Cell Nuclei: Report from a Single Institution

Abstract: Philadelphia chromosome-positive (Ph+) acute lymphoblastic leukemia (ALL) may include the lymphoid blast crisis of chronic myeloid leukemia (CML-BC). We applied fluorescence in situ hybridization (FISH) of the BCR-ABL fusion gene to peripheral blood and/or bone marrow smears to determine whether the fusion was restricted to mononuclear cell nuclei or if segmented cell nuclei representing mature neutrophils also carried the fusion (Seg-FISH). Among 20 patients with Ph+ ALL without a prior diagnosis of CML, 9 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…Therefore, the analysis of other cell types or different differentiation stages between uni-Ph and multi-Ph may be necessary to observe genetic phenotypes. Survival rates were significantly different between patients with uni-Ph and those with multi-Ph, consistent with a previous smallscale study (2). The better survival rate observed for patients with multi-Ph may be due to differences in the cell differentiation stage affected by TKI treatment between the two lineages, instead of specific genetic differences in leukemic cells.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, the analysis of other cell types or different differentiation stages between uni-Ph and multi-Ph may be necessary to observe genetic phenotypes. Survival rates were significantly different between patients with uni-Ph and those with multi-Ph, consistent with a previous smallscale study (2). The better survival rate observed for patients with multi-Ph may be due to differences in the cell differentiation stage affected by TKI treatment between the two lineages, instead of specific genetic differences in leukemic cells.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we used multiple approaches to confirm the heterogeneity of adult Ph+ALL according to BCR-ABL expression lineages (1,2). BCR-ABL signals were observed outside of leukemic blast cells in 36% of patients with Ph+ALL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our patient, we therefore performed interphase FISH analysis for BCR‐ABL1 rearrangement in blood neutrophils, which was positive allowing us to render the diagnosis of lymphoid blast crisis of CML. Consistent with our data, Kamoda et al demonstrated that, among 20 patients with BCR‐ABL1 positive ALL, detection of BCR‐ABL1 rearrangement in segmented cell nuclei was positive in 9 cases with evidence for diagnosis of lymphoid blast crisis of CML: higher rate of p210 transcript, higher white cell and blast counts, and higher rate of myeloid and T‐lymphoid antigen expression. Furthermore, Kamoda et al suggested a greater progression‐free and overall survivals in lymphoid blast crisis of CML than in de novo BCR‐ABL1 positive ALL.…”
Section: Discussionsupporting
confidence: 92%